Lejong Culture in Empowering Horticultural Farmer Groups in Golo Worok Village Ruteng Sub-District Manggarai District - Inosensius Harmin Jandu; Fabianus Gangkur; Wigbertus Gaut Utama; Polikarpus Payong (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The research was conducted to find out whether Lejong culture can empower the Golo Worok village farmer group, especially in terms of increasing human resources, such as skills and knowledge of economic fiber. The problem in this research focuses on how Lejong culture influences the capabilities of farmer groups in Golo Worok Village, Ruteng District, and Manggarai Regency. This research aims to find out how the influence of the non-governmental organization Ayo Indonesia empowers the Golo Worok Village Farmer Group and how the Farmer Group feels the process and its impacts. The data used in the research are primary data and secondary data. To obtain primary data, observation and interview methods were used. Secondary data was obtained through several kinds of literature according to research needs. The research results show that Lejong culture significantly influences the empowerment of Golo Worok Village farmer groups and that socialization and discussion are approaches packaged in Lejong culture. It is recommended that all stakeholders collaborate to optimize Lejong as a strategy to empower farmers.